Germ cell quantification in human fetal and prepubertal testis tissues: a comparison of current methodologies - Emma Kearney; David Greenald; Gabriele Matilionyte; Sheila Lane; Melissa D Tharmalingam; Jill Davies; Jan-Bernd Stukenborg; Grace Forsyth; Rod T Mitchell (Reproduction and Fertility, 2025)
Methods to quantify germ cell number in human immature testicular tissues are essential to evaluate the impact of chemotherapy exposures and to optimise cryopreservation protocols used in fertility preservation for prepubertal boys. Established quantification methods rely on the presence of round tubules within the tissue. However, round tubular cross sections are limited in human prepubertal testicular tissues, especially when using in vitro culture. We aimed to assess whether an alternative method of germ cell quantification would provide similar results to recently established methods, without the requirement for round tubules. Human testicular samples included fetal tissue (exposed in vitro to cisplatin, carboplatin or control) or prepubertal tissue (fresh, cryopreserved, fresh in vitro cultured or cryopreserved in vitro cultured). Immunofluorescence assessed AP2γ (gonocytes) and MAGE-A4 ((pre)spermatogonia) expression. Germ cells were quantified by tubular germ cell density (Method 1), which was compared to methods that require round tubules, including spermatogonial number per round tubular cross section (S/T) (Method 2), fertility index (Method 3) and round tubular germ cell density (Method 4). A correlation analysis between methods was performed. Method 1 is strongly and significantly correlated with Method 2 (r = 0.838, P < 0.0001; r = 0.833, P < 0.0001), Method 3 (r = 0.752, P < 0.001; r = 0.802, P < 0.0001) and Method 4 (r = 0.863, P < 0.0001; r = 0.914, P < 0.0001) for fetal and prepubertal tissues, respectively. Given that Method 1 assess tubules irrespective of shape, it may increase the total number of germ cells available for quantification, validating its use for quantification of human testicular tissue samples where the amount of tissue or presence of round tubules is limited.